Eternal E-Waste Lifecycle Management: A Classified Review - Maharajpet, Sheela; P, Manyatha; Namratha (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
With the threats to human health and the environment posed by the exponential growth in electronic devices, e-waste management has become a crucial global concern. The amount of electronic trash is growing, and traditional linear methods of consumption and disposal have not been able to keep up, endangering public health, and the environment, and depleting resources. In response, the idea of "eternal e-waste management" presents a paradigm change in the direction of circularity, stressing the ongoing repurposing, recycling, and reusing of resources in order to reduce waste production and increase resource efficiency. The extended producer responsibility (EPR) concept, which holds manufacturers responsible for the whole lifecycle of their products—from design and production to end-of-life disposal—lays the foundation of this strategy. EPR programs lessen the environmental effect of electronic products by encouraging sustainable patterns of production and consumption and by providing incentives for eco-design practices and material recovery. Furthermore, in order to make the collection, disassembly, and recycling of electronic trash easier, everlasting e-waste management depends on infrastructural development and technical innovation. By allowing the extraction of valuable materials from e-waste streams, advanced recycling methods including mechanical shredding, chemical treatment, and metallurgical procedures minimize environmental damage and the demand for virgin resources. Governments adopt rules, incentives, and awareness programs to encourage responsible e-waste disposal and recycling practices. Policy interventions are vital in fostering everlasting e-waste management. In order to handle transboundary e-waste flows and unify regulatory regimes across jurisdictions, international cooperation and coordination are also crucial. To sum up, everlasting e-waste management provides a comprehensive and long-term solution to the expanding problem of electronic trash. Embracing circularity, encouraging technological innovation, and putting supportive regulations in place can help societies move forward toward a more resource-efficient and sustainable future while lessening the negative effects of e-waste on the environment and human health.